Atypical Teratoid Rhabdoid Tumor: Current Therapy and Future Directions - Ginn, Kevin F.; Gajjar, Amar (Frontiers in Oncology, 2012)
Atypical teratoid rhabdoid tumors (ATRTs) are rare central nervous system tumors that comprise approximately 1-2% of all pediatric brain tumors; however, in patients less than three years of age this tumor accounts for up to 20% of cases. ATRT is characterized by loss of the long arm of chromosome 22 which results in loss of the hSNF5/INI-1 gene. INI1, a member of the SWI/SNF chromatin remodeling complex, is important in maintenance of the mitotic spindle and cell cycle control. Overall survival in ATRT is poor with median survival around 17 months. Radiation is an effective component of therapy but is avoided in patients younger than three years of age due to long term neurocognitive sequelae. Most long term survivors undergo radiation therapy as a part of their upfront or salvage therapy, and there is a suggestion that sequencing the radiation earlier in therapy may improve outcome. There is no standard curative chemotherapeutic regimen, but anectdotal reports advocate the use of intensive therapy with alkylating agents, high dose methotrexate, or therapy that includes high dose chemotherapy with stem cell rescue. Due to the rarity of this tumor and the lack of randomized controlled trials it has been challenging to define optimal therapy and advance treatment. Recent laboratory investigations have identified aberrant function and/or regulation of cyclin D1, aurora kinase, and insulin-like growth factor pathways in ATRT. There has been significant interest in identifying and testing therapeutic agents that target these pathways.